Directly administered antiretroviral therapy for HIV-infected drug users does not have an impact on antiretroviral resistance: results from a randomized controlled trial. - Maru, Duncan Smith-Rohrberg; Kozal, Michael J; Bruce, R Douglas; Springer, Sandra A; Altice, Frederick L (Journal of acquired immune deficiency syndromes (1999), 2007)
Directly administered antiretroviral therapy (DAART) is an effective intervention that improves clinical outcomes among HIV-infected drug users. Its effects on antiretroviral drug resistance, however, are unknown.
Keywords: Adult; Anti-Retroviral Agents; Drug Resistance, Viral; Drug Therapy; Female; HIV Infections; HIV-1; Humans; Male; Middle Aged; Prospective Studies; Self Administration; Substance-Related Disorders; Treatment Outcome